Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's analyze each step Jerry took in solving the equation \( 3\left(x - \frac{1}{4}\right) = \frac{13}{6} \):
1. Starting with the given equation:
[tex]\[ 3\left(x - \frac{1}{4}\right) = \frac{13}{6} \][/tex]
Jerry correctly distributed the 3:
[tex]\[ 3x - \frac{3}{4} = \frac{13}{6} \][/tex]
2. To isolate \( x \), Jerry added \( \frac{3}{4} \) to both sides. This step looks like:
[tex]\[ 3x - \frac{3}{4} + \frac{3}{4} = \frac{13}{6} + \frac{3}{4} \][/tex]
This is correct since adding \( \frac{3}{4} \) balances the equation.
3. Next, Jerry combined the fractions on the right side:
[tex]\[ 3x = \frac{13}{6} + \frac{3}{4} \][/tex]
To add these fractions, Jerry needed a common denominator. The least common denominator (LCD) of 6 and 4 is 12:
[tex]\[ \frac{13}{6} = \frac{26}{12} \][/tex]
[tex]\[ \frac{3}{4} = \frac{9}{12} \][/tex]
Adding these gives:
[tex]\[ 3x = \frac{26}{12} + \frac{9}{12} = \frac{35}{12} \][/tex]
4. Therefore, step 4 (simplifying to \( 3x = \frac{35}{12} \)) is correct:
[tex]\[ 3x = \frac{35}{12} \][/tex]
5. However, in step 5, Jerry mistakenly multiplied by \( \frac{3}{1} \) instead of dividing both sides by 3 (or multiplying by \( \frac{1}{3} \)):
[tex]\[ 3x = \frac{35}{12} \][/tex]
To solve for \( x \), we should divide both sides by 3:
[tex]\[ x = \frac{\frac{35}{12}}{3} = \frac{35}{12} \cdot \frac{1}{3} = \frac{35}{36} \][/tex]
Based on this detailed analysis, Jerry made the error in step 5. Thus, the error occurs in step 5, where Jerry should have multiplied both sides by [tex]\( \frac{1}{3} \)[/tex].
1. Starting with the given equation:
[tex]\[ 3\left(x - \frac{1}{4}\right) = \frac{13}{6} \][/tex]
Jerry correctly distributed the 3:
[tex]\[ 3x - \frac{3}{4} = \frac{13}{6} \][/tex]
2. To isolate \( x \), Jerry added \( \frac{3}{4} \) to both sides. This step looks like:
[tex]\[ 3x - \frac{3}{4} + \frac{3}{4} = \frac{13}{6} + \frac{3}{4} \][/tex]
This is correct since adding \( \frac{3}{4} \) balances the equation.
3. Next, Jerry combined the fractions on the right side:
[tex]\[ 3x = \frac{13}{6} + \frac{3}{4} \][/tex]
To add these fractions, Jerry needed a common denominator. The least common denominator (LCD) of 6 and 4 is 12:
[tex]\[ \frac{13}{6} = \frac{26}{12} \][/tex]
[tex]\[ \frac{3}{4} = \frac{9}{12} \][/tex]
Adding these gives:
[tex]\[ 3x = \frac{26}{12} + \frac{9}{12} = \frac{35}{12} \][/tex]
4. Therefore, step 4 (simplifying to \( 3x = \frac{35}{12} \)) is correct:
[tex]\[ 3x = \frac{35}{12} \][/tex]
5. However, in step 5, Jerry mistakenly multiplied by \( \frac{3}{1} \) instead of dividing both sides by 3 (or multiplying by \( \frac{1}{3} \)):
[tex]\[ 3x = \frac{35}{12} \][/tex]
To solve for \( x \), we should divide both sides by 3:
[tex]\[ x = \frac{\frac{35}{12}}{3} = \frac{35}{12} \cdot \frac{1}{3} = \frac{35}{36} \][/tex]
Based on this detailed analysis, Jerry made the error in step 5. Thus, the error occurs in step 5, where Jerry should have multiplied both sides by [tex]\( \frac{1}{3} \)[/tex].
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.